2015
DOI: 10.1097/mbc.0000000000000315
|View full text |Cite
|
Sign up to set email alerts
|

Induction therapy alters plasma fibrin clot properties in multiple myeloma patients

Abstract: Induction therapy in patients with multiple myeloma increases the risk of thromboembolism. We have recently shown that multiple myeloma patients tend to form denser fibrin clots displaying poor lysability. We investigated the effect of induction therapy on fibrin clot properties in multiple myeloma patients. Ex-vivo plasma fibrin clot permeability, turbidity, susceptibility to lysis, thrombin generation, factor VIII and fibrinolytic proteins were compared in 48 multiple myeloma patients prior to and following … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
26
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 27 publications
1
26
0
Order By: Relevance
“…Current consensus guidelines recommend pharmacological thromboprophylaxis for subgroups of ambulatory patients with myeloma receiving treatment (provided the bleeding risk is favorable), although little evidence exists to guide duration of this therapy. 5,6 While the interpretation of our results is limited by the lack of a correlation with clinical outcomes, the suggestion that the thrombotic risk associated with active myeloma might diminish at an early stage of antimyeloma therapy reflects other recently published studies of evolving hypercoagulability in myeloma 47 and may have future implications for thromboprophylaxis strategies and patient risk stratification in this disease.…”
Section: Discussionmentioning
confidence: 60%
“…Current consensus guidelines recommend pharmacological thromboprophylaxis for subgroups of ambulatory patients with myeloma receiving treatment (provided the bleeding risk is favorable), although little evidence exists to guide duration of this therapy. 5,6 While the interpretation of our results is limited by the lack of a correlation with clinical outcomes, the suggestion that the thrombotic risk associated with active myeloma might diminish at an early stage of antimyeloma therapy reflects other recently published studies of evolving hypercoagulability in myeloma 47 and may have future implications for thromboprophylaxis strategies and patient risk stratification in this disease.…”
Section: Discussionmentioning
confidence: 60%
“…In contrast, in Crowley et al study including 10 patients before and during myeloma treatment (at 1, 2, and 3 months), thrombin generation was significantly decreased during treatment, as evidenced by a significant decrease in peak thrombin at 3 months of treatment compared with baseline . Similarly, Undas et al also demonstrated a significant decrease in peak thrombin at 3 months of treatment in 48 patients …”
Section: Discussionmentioning
confidence: 89%
“…It must be emphasized that during follow‐up, no thromboembolic events have been reported, except a symptomatic pulmonary embolism in one patient which occurred at diagnosis. However, the overall rate of thrombotic events during MM treatment varied between 10% and 25% depending on the series despite the thromboprophylaxis …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A low concentration of TF was used to maximize the possibility of evidencing hypercoagulability while taking into account factor VIII levels, which are known to be high and even very high in patients with MM 27,28. The predisposition of patients with MM to thrombosis could be due to changes in endothelium, leukocytes, fibrin structure and lysis,29,30 which are not captured by TG studies. Incidence of thromboembolic events, acute cardiovascular events and bleeding…”
mentioning
confidence: 99%